Age-dependent Skill Formation and Returns to Education - Friedhelm Pfeiffer; Karsten Reuß (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
In this study, we try to connect the economic literature on human capital formation with findings from neurobiology and psychology on early childhood development and self-regulation. Our basic framework for assessing the distribution of agespecific returns to investment in skills is an elaboration of the model of skill formation from Cunha, Heckman et al. (2006) over the life cycle. Our simulation based evidence illustrates the cumulative and synergetic nature of skill formation, the skill multiplier and the shaping role early childhood has for human capital formation, growth and inequality.
Keywords: J21; J31; J24; 330; Intelligence; self-regulation; human capital; returns to education; life span